2022
DOI: 10.1186/s13578-022-00792-9
|View full text |Cite
|
Sign up to set email alerts
|

LRP4 is required for the olfactory association task in the piriform cortex

Abstract: Background Low-density lipoprotein receptor-related protein 4 (LRP4) plays a critical role in the central nervous system (CNS), including hippocampal synaptic plasticity, maintenance of excitatory synaptic transmission, fear regulation, as well as long-term potentiation (LTP). Results In this study, we found that Lrp4 was highly expressed in layer II of the piriform cortex. Both body weight and brain weight decreased in Lrp4ECD/ECD mice without TMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…However, surprisingly, we have found that the protective effect exerted by digoxin seems to be unrelated to the inhibition of Na + /K + -ATPase ( Supplementary Figure 1A ). Low-density lipoprotein receptor-related protein 4 (LRP4) is a transmembrane protein involved in various cellular processes, including cell adhesion, migration, and signal transduction ( 29 , 30 ). Recent studies have indicated that LRP4 is a novel target involved in digoxin-mediated regulation of cartilage metabolism ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, surprisingly, we have found that the protective effect exerted by digoxin seems to be unrelated to the inhibition of Na + /K + -ATPase ( Supplementary Figure 1A ). Low-density lipoprotein receptor-related protein 4 (LRP4) is a transmembrane protein involved in various cellular processes, including cell adhesion, migration, and signal transduction ( 29 , 30 ). Recent studies have indicated that LRP4 is a novel target involved in digoxin-mediated regulation of cartilage metabolism ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…CHSY1 is indispensable for skeletal development and the promotion of bone length (Wilson et al, 2012). MDK and LEF1 assume vital roles in cartilage development, skeletal growth, and osteoblast differentiation and regeneration (Haffner-Luntzer et al, 2016;Yan et al, 2022). In the context of GO:0042475 (odontogenesis of dentin-containing tooth), the key genes WNT6, LEF1, LRP4, and TP63 play pivotal roles in dental cell differentiation, skeletal development, and osteoblast differentiation (Ahn et al, 2017;Luo et al, 2019;Wei et al, 2020;Gong et al, 2021).…”
Section: Exploring the Regulatory Mechanisms Of High-altitude Adaptiv...mentioning
confidence: 99%
“…WB was performed as previously described, with minor modifications [35]. In brief, the cells were collected, and the proteins were extracted via RIPA (1.0% NP-40, 150 mm NaCl, 50 mm pH 8.0 Tris, 0.5% Na-deoxycholate, 0.1% SDS), supplemented with 1% PMSF (Phenyl-methane sulfonyl fluoride) and protease inhibitor cocktail (Cat.…”
Section: Western Blotting (Wb)mentioning
confidence: 99%